Infecção de cães por inoculação experimental com isolados humanos de Giardia duodenalis: manifestações clínicas e laboratoriais - Rosa, Luiz Antonio Goiabeira (2005)
The potential health risk for humans in relation to parasites from dogs is an important issue worldwide (SCHANTZ, 1994). This is applied to well-documented diseases, such as visceral larva migrans syndrome, and to emerging and reemerging infections, such as cryptosporidiosis and giardiasis, respectively (SCHANTZ, 1991). Protozoa are considered an important public health problem, due to their wide distribution, occurrence and high resistance to preventive measures. Among these, Giardia duodenalis is one of the main parasites in humans, being the most frequent protozoan agent of intestinal disease in several countries and referred to as the main non-viral cause of diarrhea, commonly identified in epidemics (THOMPSON et al., 2000; LANE & LLOYD, 2002). Found in the intestinal tract of humans and various animals worldwide as mammals, reptiles, amphibians and birds, it can cause a disease called giardiasis, recognized since 1979 as zoonosis by the World Health Organization (WHO, 1979), although many scientists disagree with this. position. Discovered by Anton Van Leeuwenhoeck in 1681, the binucleated flagellated protozoan Giardia spp. belongs to the phylum Sarcomastigophora, class Zoomastigophorea, order Diplomonadida, family Hexamitidae. Until the middle of the 20th century, more than 50 species were described, making the taxonomy of Giardia spp. complicated and confusing. For a long time it was classified according to the species of the host where it was found (LANE & LOYD, 2002), being Giardia bovis in cattle, Giardia canis in dogs, Giardia lamblia in man, Giardia cati in cats (KENNEDY.1989). From 1952, based on the protozoan morphology and structure, FILICE identified three distinct types, defining three species called Giardia agilis, amphibian parasite, Giardia muris of rodents, possibly birds and mammals and Giardia duodenalis (synonym G. lamblia, G.intestinalis), found in mammals, possibly birds and reptiles. Two additional species were later found in birds, Giardia psittaci (ERLANDSEN & BEMRICK, 1987) and Giardia ardeae (ERLANDSEN et al. 1990), described according to structural characteristics identified in trophozoites and observations through electron microscopy. A sixth species, Giardia microti (wild animals), has been proposed based on the cyst morphology (FEELY, 1988) and on analysis of the sequence of rRNA subunits (van KEULEN et al, 1998). Despite the similarities, the morphological similarity masks genetic and phenotypic differences, sufficient for Giardia duodenalis to be considered a complex of species. Through phylogenetic analysis, seven main underlines (from A to G) representing widely distributed genotypes were defined (THOMPSON et al., 2000; MONIS et al., 2003). Studies using phenotypic and genetic criteria, demonstrate that isolates recovered from humans and many other mammalian species belong to one of two of these underlines, called Assemblages A and B, or Polish and BeJgian, respectively (THOMPSON et al., 2000). It has a worldwide distribution, with children under five and adults between 25 and 39 years of age the most affected human age groups. Giardia duodenaiis is a serious disease in developing countries and the main cause of intestinal infection in developed countries, causing around 2.8 x 108 annual cases in humans (LANE & LLOYD, 2002). About 200 million people in Asia, Africa and Latin America have symptoms of giardiasis with 500,000 new cases each year (WHO, 1996). It is one of the most common parasites in domestic dogs. These are commonly infected, whether they are pet, stray or kennel dogs (SCHANTZ, 1999; BUGG et al., 1999; PAPINI et al., 2005). Although the finding of Giardia duodenalis in dogs is frequent, the apparent clinical disease is rare (BARR & BOWMAN, 1994, THOMPSON, 2004). Giardiasis can be severe in young dogs, negatively affecting growth (DIAZ-SAEZ et al, 1996). Studies reveal considerable variation in prevalence, with the highest infection rates observed in puppies (HAHN, 1988, DIAZ-SAEZ et al., 1996). The importance of infection with Giardia duodenalis is shown by its prevalence, severity of the disease (when it occurs), zoonotic potential and difficulty in diagnosis, as well as little efficacy and side effects of the drugs used in the treatment (BARR & BOWMAN, 1994). The possibility of transmission of parasites between pet dogs and their owners depends on the genotype of Giardia duodenalis. Infection by the protozoan in dogs is significant in public health and its zoonotic potential must be taken into account (THOMPSON, 2000, 2004). The biggest issue involving giardiasis is about its zoonotic character. In relation to public health, the greatest risk involves genotypes present in Assemblage A e em menor extensão genótipos de Assemblage B. O genótipo grupo I de Assemblage A and to a lesser extent genotypes of Assemblage B. The group I genotype of Assemblage A is proven to be infectious to men and animals (MONIS & THOMPSON, 2003). It is not clear whether genotypes of Assemblage B, or Belgian, represent zoonosis (MACOTELAA, 2002). Genotypes of Giardia duodenalis found in humans have also been detected in the environment and in several species of domestic and wild animals, confirming the spread of Giardia in nature and showing that there is a possibility of zoonosis (VAN KEULEN et al., 2002; THOMPSON, 2004). Whether animals function as reservoirs for humans or vice versa, it is an undefined question to be resolved in studies on the parasite. The type of Giardia duodenalis that affects humans can be transmitted experimentally to several animal species, but the transmission of animals to humans is a controversial subject, and the specific role of dogs in human giardiasis has not yet been established (MONIS & THOMPSON, 2003).